2014
DOI: 10.1016/j.neuroscience.2014.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Early exposure to bisphenol A alters neuron and glia number in the rat prefrontal cortex of adult males, but not females

Abstract: Previous work has shown that exposure to bisphenol A (BPA) during early development can alter sexual differentiation of the brain in rodents, although few studies have examined effects on areas of the brain associated with cognition. The current study examined if developmental BPA exposure alters the total number of neurons and glia in the medial prefrontal cortex (mPFC) in adulthood. Pregnant Long-Evans rats were orally exposed to 0, 4, 40, or 400 μg/kg BPA in corn oil throughout pregnancy. From postnatal day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 104 publications
1
25
1
Order By: Relevance
“…We did not observed a significant effect of BPA exposure on the number of neurons. This contrasts with to the findings of Sadowski et al (2014), in which perinatal BPA exposure resulted in an increase in the number of neurons in adult male rats. This indicates a difference in vulnerability during the perinatal versus adolescent period of development.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not observed a significant effect of BPA exposure on the number of neurons. This contrasts with to the findings of Sadowski et al (2014), in which perinatal BPA exposure resulted in an increase in the number of neurons in adult male rats. This indicates a difference in vulnerability during the perinatal versus adolescent period of development.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, it reverses the sex difference in the number of neurons in the locus coeruleus (Kubo et al, 2003). Few studies have investigated the effect of perinatal BPA exposure on areas of the brain associated with cognition, but Sadowski et al (2014) found an increase in the number of neurons in the adult medial prefrontal cortex (mPFC) in male, but not female, rats.…”
Section: Introductionmentioning
confidence: 99%
“…BPA is one of the toxic environmental and industrial EDCs, targets several tissues and organs, and causes hepatoxicity, immunotoxicity, genotoxicity, neurotoxicity, and mutagenic and carcinogenic effects [65]. BPA interferes with several molecular, neurochemical, and cellular events occurring during the normal development of the brain [66][67][68]. Recently, we have shown that BPA reduces myelination and neurogenesis in the hippocampus region via inhibition of the Wnt/β-catenin pathway, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is robust evidence that BPA exposure can disrupt hippocampal neural circuitry (Bowman et al, 2014; Elsworth et al, 2013; Hajszan and Leranth, 2010; Kim et al, 2011; Leranth et al, 2008a; Leranth et al, 2008b; Tiwari et al, 2014; Xu et al, 2013; Xu et al, 2014; Zhang et al, 2014). Conversely, the differential behavioral effects of BPA might be due to effects on other brain regions, such as the prefrontal, orbitofrontal, retrosplenial cortex, medial septum, ventral septum, thalamus, nucleus accumbens, and amygdala (Arias et al, 2014; Czajkowski et al, 2014; Jankowski et al, 2013; Rinaldi et al, 2012), and several other areas which have been shown to be vulnerable to BPA effects (Cao et al, 2014; Cao et al, 2013; Facciolo et al, 2002; Sadowski et al, 2014b). The behavioral disruptions may also originate from sex-dependent epigenetic changes in the brain (Jasarevic et al, 2012; Kundakovic et al, 2013; Yaoi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%